Effective Route Analysis For Petrol Delivery And System Optimization Using Arena Simulation - Mazlan, Nurul Atiqah (2021)
Oil is extracted and stored in the depot and will be sent to the petrol station. Usually, depots are located far from petrol stations. Therefore, one of the problems that has been considered is the time travel that takes a long-time causing gas stations to run out of fuel and hence reduce profits. In that case, depot needs to reconsider alternative routes to compare the cost and distance effectiveness of petrol tankers to Petrol Station XYZ to achieve the vision of Penang 2030 to become an integrated green and smart state that will empower the country, by reducing carbon emissions. Next, another problem that occurs in the management system is in terms of waiting time and service time for customers which are too long. Simulations are needed to describe real situations and to calculate performance of Petrol Station XYZ. In addition, additional simulations need to be performed to determine performance if cash payment counters are added. Therefore, this study applying Dijkstra Algorithms and Queuing System to solve the problems. Simulations have been done using QGIS Software and the results show that there are three alternative routes that can be used to ship fuel to Petrol Station XYZ. The shortest route is Route 1 (existing route) which uses the first bridge of Penang. ARENA Simulation results help to understand the performance of Petrol Station XYZ. The results show that the average waiting time at peak hours is higher than normal hours because the probability of customers paying in cash is higher than using a card and there is only one cash payment counter.